INTERFERON TREATMENT OF HEPATITIS C - KOGA, Michiaki; YATSUHASHI, Hiroshi; YANO, Michitami; INOKUCHI, Kaoru; MATSUMURA, Nobuyuki; INOUE, Osami (Japanese Journal of National Medical Services, 1993)
Thirty percent of the patients who underwent interferon treatment showed the continuous normalization of ALT level and the continuous disappearance of HCV-RNA from serum and they were regarded as clinical cure. HCV-RNA level and HCV genotype had a connection with the prediction for IFN response. HCV-RNA level was a more important factor than HCV-genotype.